Konstitusi Rigid dan Fleksibel: Analisis Komparatif dalam Sistem Civil Law dan Common Law: Rigid and Flexible Constitutions: A Comparative Analysis of Civil Law and Common Law Systems - Yusuf Saeful Hayat; Romadhon; Utang Rosidin (SIYASI: Jurnal Trias Politica, 2024)
This study examines the implications of constitutional flexibility on governance using a comparative law method with a normative-historical approach. The focus is on comparing rigid and flexible constitutions in Civil Law and Common Law systems, along with case studies of amendments to Indonesia’s 1945 Constitution and constitutional reforms in the United Kingdom. Findings indicate that rigid constitutions provide political stability and legal certainty but adapt slowly to socio-political changes, whereas flexible constitutions allow rapid adaptation, though they may pose potential legal instability if not properly controlled. The study highlights the importance of balancing stability and flexibility through selective reforms, checks and balances, and public participation. These findings offer recommendations for lawmakers and policymakers to adjust amendment mechanisms to maintain equilibrium between stability and adaptability